Integrative Islamic Education for Organizational Cadre Formation: A Case Study of Muhammadiyah Boarding School in Trenggalek, Indonesia - Ngumar Ngumar; Tobroni Tobroni; Romelah Romelah; Afiful Ikhwan (AL-ISHLAH: Jurnal Pendidikan, 2025)
This study investigates the cadre development process within the Muhammadiyah organization through Islamic education at the Muhammadiyah Boarding School (MBS) in Trenggalek Regency. Cadre formation is a critical aspect of organizational sustainability, yet limited research has explored how Islamic educational institutions facilitate this process. Using a qualitative research design, data were collected through observation, in-depth interviews, and documentation to explore three key areas: the implementation of educational programs for cadre development, the integration of Islamic curriculum with leadership and organizational training, and the outcomes of these programs for Muhammadiyah's regeneration. The findings reveal that MBS Trenggalek systematically integrates Muhammadiyah values into both formal education and daily student life. Educational activities emphasize religious devotion, academic excellence, character development, and leadership training. These elements are embedded within a curriculum that balances spiritual instruction with practical organizational experience. Results indicate that MBS graduates exhibit strong religious commitment, scholastic achievement, and a deep sense of organizational loyalty. Many alumni actively participate in Muhammadiyah institutions, demonstrating leadership capacity and ideological alignment. This study underscores the role of integrative Islamic boarding school programs in shaping future organizational leaders. It contributes to the broader discourse on faith-based education by presenting MBS as a model for ideological regeneration within Islamic movements, addressing a gap in the literature on how education serves as a strategic tool for long-term cadre development.